Mathematical reasoning ability of students based on learning style using Missouri Mathematics Project learning model - Wahyudi, Indra Dana; Walid, Walid (Unnes Journal of Mathematics Education, 2020)
The purpose of this study is to (1) determine whether student learning outcomes in aspects of mathematical reasoning ability using the Missouri Mathematics Project learning model achieve classical completeness criteria, (2) describe the mathematical reasoning ability in terms of learning styles using the Missouri Mathematics Project learning model. The method used is mixed methods explanatory sequential design with a population of students in one of senior high school in Demak in the academic year 2019/2020. Samples were taken by cluster random sampling and obtained XI Mathematics dan Science 4 as an experimental class. The research subjects were taken with a purposive sampling technique selected based on the learning style category and obtained 6 subjects. The research data was taken by using test, questionnaire, and interview techniques. The results showed (1) The ability of mathematical reasoning on the application of the Missouri Mathematics Project learning model achieved classical completeness; (2) Two types of visual learning style subjects have mathematical reasoning abilities at the medium and low levels; (3) Two types of auditory learning style subjects have mathematical reasoning abilities at high and low levels; (4) Two types of kinesthetic learning style subjects have mathematical reasoning abilities at high and low levels; (5) The average results of the ability tests for each learning style show that students with auditory learning styles have the highest average.